MANIFESTASI KETIDAKADILAN GENDER DALAM SASTRA LISAN KABA - Ananda, Refisa; Olva Zuve, Farel; Syafruddin (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2024)
Gender inequality breeds a variety of injustices. Kaba oral literature contains the perspective of the Minang people on social and cultural life. This study aims to describe the sweetness of gender injustice in Kaba Urang Tanjuang Karang. The method used in this study is the descriptive-analysis method. Data collection is carried out by recording and transcribing kaba. So, the data of this study is the result of transcription of the Kaba Urang Tanjung Karang manuscript. The results showed that gender inequality gave birth to various injustices, especially for female figures in the Tanjung Karang Urang Regency. The injustice experienced by the figures of Amak Delima, Siti Delima, Unyiang, Mak Lapau dan Siti Rohani manifest in five forms, namely marginalization, subordination, stereotypes, violence, and double burdens. These forms of gender injustice are experienced by female characters who have roles as mothers, wives, children, or older siblings.